Penerapan Strategi Marketing dalam Meningkatkan Pelanggan di Toserba Sunan Drajat (Studi di Toserba Sunan Drajat Banjarwati Paciran Lamongan) - Putri, Rizqi Ananda; Abdullah Zawawi; Maghfur, Arif (Al-Muzdahir : Jurnal Ekonomi Syariah, 2023)
The development of the business world is growing rapidly both in the service and industrial sectors. This causes competition between companies to become increasingly stringent. This requires companies to improve their capabilities so that the products or services produced are increasingly innovating. So in the process a marketing strategy is needed to improve the development of the business. This type of research uses qualitative research methods with a descriptive approach which is obtained through collecting data from the process of observation, interviews/interviews, and documentation. While the data analysis technique used is data reduction, data presentation, and conclusion. The purpose of this research is to answer, find out, describe and analyze the formulation of the problem; 1) at the Sunan Drajat Banjarwati Paciran Lamongan Department Store. 2) How to plan the implementation of the marketing strategy at the Sunan Drajat Banjarwati Paciran Lamongan Department Store. 3) What are the supporting and inhibiting factors encountered in marketing products at the Sunan Drajat Department Store Banjarwati Paciran Lamongan. The analysis used is the Marketing Mix analysis approach with seven indicators from an internal and external perspective. In addition, it is strengthened by Segmentation, Targeting and Positioning which are collaborated on the analysis of the application of marketing strategies at the Sunan Drajat Department Store. The results of the study explain that the Sunan Drajat Department Store applies a marketing mix strategy, namely product, place, price, promotion, people, processes, physical evidence and in its development also apply segmentation, targeting, and positioning in it.